AN ELUCIDATION OF THE POSITION OF WOMEN BEFORE THE ADVENT OF ISLAM AS DESCRIBED IN THE GLORIOUS QUR’AN - Abubakar Ibrahim Usman (Spektra: Jurnal Ilmu-ilmu Sosial, 2023)
Before the advent of Islam, the position of women varied widely across different regions and cultures. It is important to note that the following information provides a general overview and may not apply uniformly to all societies of that time. Pre-Islamic Arabia: In pre-Islamic Arabia, women's status varied greatly depending on tribal customs and traditions. Some tribes practiced female infanticide, considering daughters a burden, while others valued women as members of the community. Women were often married off at a young age and had limited rights in matters of inheritance, divorce, and property ownership. Polygamy was prevalent, and women were sometimes treated as objects of trade. The position of women in pre-Islamic Arabia was varied, depending on their social status and tribal affiliation. However, in general, women had few rights and were often treated as second-class citizens. They were not allowed to own property, inherit, or testify in court. They could be married off without their consent, and they could be divorced by their husbands at will. Therefore, the aim of this paper is to expose these issues in details. Also, the paper explains the status of women in Roman period, in Jews period and in the Christian era. The method used in conducting this research is analytical method.